Influence of Sr on mechanical properties of Al-2%Si alloys during eutectic solidification - Sakamoto, Toshio; Hirano, Rio; Faiz, Muhammad Khairi; Yoshida, Makoto; Nagata, Yoshihiro; Okane, Toshimitsu; Ozaki, Shogo; Orio, Kanta; Okimura, Yasuhiko; Matsushita, Akira (Journal of Japan Institute of Light Metals, 2023)
Al-Si alloys have lower hot tearing susceptibility (HTS) than other aluminum alloys. However, hot tearing occurs under certain casting conditions. It is known that the Sr addition reduces the HTS because of the enhancement of crack-healing. Meanwhile, an influence of Sr addition on the tensile strength, ductility, and viscous properties during eutectic solidification has not yet been clarified. In this study, we investigated the influence of Sr addition on these properties during eutectic solidification. The tensile tests during eutectic solidification were conducted for Al-2Si and Al-2Si-Sr alloys. The results show that the Sr addition did not affect the viscous properties. On the other hand, the tensile strength and elongation during the latter half of eutectic solidification increased by Sr addition. Consequently, the HTS reduction by Sr addition should be attributed to the improvement of ductility. It was suggested that the increase in the elongation by Sr addition should result from the decrease in the tensile stress, which affects the opening and propagation of hot tearing, due to the increase in porosity near the crack.